Heat gain from power panelboard - Piesciorovsky, Emilio Carlos (Kansas State University, 2009)
This thesis focuses on estimating the power loss from power panelboards by means of power loss models. The model is intended to be used by HVAC engineers to help estimate building heat loss. While McDonald & Hickok (1985) did not report power losses for power panelboards, Rubin (1979) did. These publications present the power losses of electrical devices at rated loads in tables. In this thesis, the models for electrical devices are created and used, instead of tables, to estimate power losses. The use of curve fit models presents a convenience in calculation of power losses. Breaker, fusible switch, and motor starter power losses presented by McDonald & Hickok (1985) and Rubin (1979) were updated using manufacturer published data, technical papers, industrial standards, and test samples. Test, manufacturer, and analytical model data are collected and power loss curve fit models are created for breakers, fusible switches, motor starters, and bus bars with enclosures. The panelboard power loss is calculated as the sum of partial power losses of the component electrical equipment, i.e. breakers, fusible switches, motor starters, and bus bars with enclosures used in power panelboards. A power loss model for main breaker and fusible switch power panelboards are created based on the sum of breaker, fusible switch, motor starter, and bus bars with enclosure power loss models. The main breaker and fusible switch power panelboard power loss models are used in a heat loss example. It is shown that power panelboard power losses can be significantly overestimated when calculated with one of the methods currently used (Rubin, 1979). This can result in erroneous sizing of HVAC equipment.
Keywords: Heat gain; Power loss; Panelboard; Panel board; Engineering, Electronics and Electrical (0544); Engineering, General (0537); Engineering, Mechanical (0548)